Characterization of a Novel Esterase Est33 From an Antarctic Bacterium: A Representative of a New Esterase Family - Liu, Xiaoyu; Zhou, Mingyang; Sun, Rui; Xing, Shu; Wu, Tao; He, Hailun; Chen, Jianbin; Bielicki, John Kevin (Frontiers in Microbiology, 2022)
Studies of microorganisms from extreme environments can sometimes reveal novel proteins with unique properties. Here, we identified a novel esterase gene (Est33) from an Antarctic bacterium. The protein was expressed and purified for biochemical characterizations. Site-mutation variants including S94A, D205A, and H233A were constructed to explore the structure-function relationship of the catalytic triad of Est33, and we found mutating Ser94, Asp205, and His233 residues lead to a complete loss of enzyme activity. In addition, the catalytic Ser94 located in a conserved pentapeptide motif GVSWG. Phylogenetic analysis showed that Est33 and its closely related homologs belonged to an independent group apart from other known family members, indicating that Est33 represented a new family of esterase. The Est33 enzyme was found to be a cold-active esterase retaining 25-100% activity from 10-30 °C, and to have optimal catalytic activity toward p-nitrophenol acetate (30°C and pH7.5). The serine modifying reagent phenylmethlsulphonyl fluoride inhibited the activity of Est33 by 77.34%, while thiol reagents such as dithiol threitol (DTT) activated the enzyme by 3-fold. Metal chelating reagents EDTA had no effects, indicating that Est33 is not a metalloenzyme. Collectively, these results indicate that Est33 constitutes the first member of a novel esterase family XXI that has been identified.